2019
DOI: 10.1002/jbmr.3883
|View full text |Cite
|
Sign up to set email alerts
|

Denosumab Prevents Early Periprosthetic Bone Loss After Uncemented Total Hip Arthroplasty: Results from a Randomized Placebo-Controlled Clinical Trial

Abstract: Implant loosening is the most common indication for revision surgery after total hip arthroplasty (THA). Although bone resorption around the implants plays a pivotal role in the pathophysiology of loosening, it is unknown whether potent early inhibition of osteoclasts could mitigate this process and thus reduce the need for revision surgery. We performed a randomized, double-blind, placebo-controlled phase 2 trial in 64 patients aged 35 to 65 years with unilateral osteoarthritis of the hip. They underwent surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
49
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 39 publications
4
49
3
Order By: Relevance
“…(9)(10)(11) The current limited data demonstrated that denosumab is at least as effective as bisphosphonates in decreasing bone resorption, and denosumab even increases bone mass in some Gruen zones, although the exact BMD changes in each Gruen zone were not given in detail in the present study. (1,2) However, both studies found that the periprosthetic BMDs of the denosumab group approached the levels of the placebo group after discontinuation of denosumab, although the rebound effect was only observed in the present study and might have been missed in the other study. (1,2) The rapid reversal after cessation of denosumab has been well documented in previous research, and bisphosphonates are recommended to prevent the subsequent rebound increase in bone resorption, which was confirmed to be valid in a recent study.…”
Section: College Beijing Chinacontrasting
confidence: 56%
See 2 more Smart Citations
“…(9)(10)(11) The current limited data demonstrated that denosumab is at least as effective as bisphosphonates in decreasing bone resorption, and denosumab even increases bone mass in some Gruen zones, although the exact BMD changes in each Gruen zone were not given in detail in the present study. (1,2) However, both studies found that the periprosthetic BMDs of the denosumab group approached the levels of the placebo group after discontinuation of denosumab, although the rebound effect was only observed in the present study and might have been missed in the other study. (1,2) The rapid reversal after cessation of denosumab has been well documented in previous research, and bisphosphonates are recommended to prevent the subsequent rebound increase in bone resorption, which was confirmed to be valid in a recent study.…”
Section: College Beijing Chinacontrasting
confidence: 56%
“…(1,2) However, both studies found that the periprosthetic BMDs of the denosumab group approached the levels of the placebo group after discontinuation of denosumab, although the rebound effect was only observed in the present study and might have been missed in the other study. (1,2) The rapid reversal after cessation of denosumab has been well documented in previous research, and bisphosphonates are recommended to prevent the subsequent rebound increase in bone resorption, which was confirmed to be valid in a recent study. (12)(13)(14)(15) Based on the current available evidence and the theoretical considerations of the pharmacodynamics of denosumab (as well as of bisphosphonates), at least two injections of denosumab every 6 months after THA should be used for preventing the rapid decreases of periprosthetic BMD within the first year.…”
Section: College Beijing Chinacontrasting
confidence: 56%
See 1 more Smart Citation
“…Over 500,000 THAs were performed in the USA annually, and the demand for THA is still growing [1].As one of the major concerns after THA, periprosthetic bone loss was closely related to aseptic loosening, periprosthetic fractures, and implant failure [2].It was reported that the mean periprosthetic bone loss was up to 21.9% 10 years post-operation [3,4]. Thus, medical intervention of periprosthetic bone loss in the immediate postoperative period was widely accepted [5,6]. However, not all the patients experienced periprosthetic bone loss after THA, especially those without osteopenia and osteoporosis [7,8].Correspondingly, identi cation of patients with increasedrisk of postoperative periprosthetic bone loss is of great value for clinical decision-makingand cost-effectiveness analysis on a patient-speci c level.…”
Section: Introductionmentioning
confidence: 99%
“…
We appreciate the comments by Shao and Wu and the opportunity to discuss the effect of denosumab on periprosthetic bone after joint replacement surgery.Shao and Wu raise three questions regarding our recent article (1) in JBMR:1What is the external validity of our study? Can our results be generalized to an older population with a higher incidence of osteoporosis?
…”
mentioning
confidence: 98%